1988
DOI: 10.1177/00220345880670110101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Casting Ring Liners on the Potential Expansion of a Gypsum-bonded Investment

Abstract: Cellulose paper (used wet) and ceramic paper (used dry) are replacing asbestos paper as cushioning ring liners in dental casting. A study was made of the effects of all three of these materials on the setting and subsequent thermal expansion of a gypsum-bonded cristobalite casting investment (WIP = 0.40). Thennal expansion measurements were made on the same specimens that were produced during the setting expansion tests.Control specimens setting against a smooth dry surface showed a total expansion of 1. 7%. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The finding from this research reconfirmed the observation of Earnshaw et al .,[27] who reported that the investment setting in dry condition improves better marginal adaptation and less distortion.…”
Section: Discussionsupporting
confidence: 90%
“…The finding from this research reconfirmed the observation of Earnshaw et al .,[27] who reported that the investment setting in dry condition improves better marginal adaptation and less distortion.…”
Section: Discussionsupporting
confidence: 90%
“…The above problems can be partially overcome with the use of a ring liner . The liner provides the needed resilience against the rigid metal ring and permits setting and thermal expansion of investment, allowing mold cavity enlargement . However, expansion provided by the liner still remains anisotropic in nature, with the axial component being greater than the lateral/radial component .…”
Section: Discussionmentioning
confidence: 99%
“…3,22 The liner provides the needed resilience against the rigid metal ring and permits setting and thermal expansion of investment, allowing mold cavity enlargement. 6,21,[25][26][27][28] However, expansion provided by the liner still remains anisotropic in nature, with the axial component being greater than the lateral/radial component. 5,28,29 The thermal expansion of the metal casting ring also undergoes expansion during heating and may additionally account for the increased marginal gaps obtained in the metal ring casting groups (IIA and IIB) in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investment expansion.-Laboratory measurements of the investment's potential expansion were made on specimens which set against each of the pre-wetted lining materials; measurements were made by continuous readings on the one specimen during setting and then duringheatingto 650'C (Earnshaw, 1988). Control measurements were also made on specimens setting without exposure to additional water (trough lined with PTFE).…”
Section: Introductionmentioning
confidence: 99%